2020
DOI: 10.3390/polym12020262
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Creep Behavior of High-Density Polyethylene Lumber and Wood Plastic Composite Lumber Made from Thermally Modified Wood

Abstract: The use of wood plastic composite lumber as a structural member material in marine applications is challenging due to the tendency of wood plastic composites (WPCs) to creep and absorb water. A novel patent-pending WPC formulation that combines a thermally modified wood flour (as a cellulosic material) and a high strength styrenic copolymer (high impact polystyrene and styrene maleic anhydride) have been developed with advantageous viscoelastic properties (low initial creep compliance and creep rate) compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In this context, the application of wood plastic composites in marine applications sounds very interesting. Alrubaie et al [39] presented an innovative wood plastic composite lumber made from thermally modified wood. Its overall performance was compared to the performance of high-density polyethylene lumber (HDPE).…”
mentioning
confidence: 99%
“…In this context, the application of wood plastic composites in marine applications sounds very interesting. Alrubaie et al [39] presented an innovative wood plastic composite lumber made from thermally modified wood. Its overall performance was compared to the performance of high-density polyethylene lumber (HDPE).…”
mentioning
confidence: 99%
“…The deflection of the samples was then slowly observed in the time interval between 50 h (3000 min) and 1000 h (60,000 min). It also found that the creep strain tended to increase with enhanced levels of loading [11,17,20]. According to the tests under different load levels of the ultimate flexural strength, it was found that the deflections of the rPP are 2.45, 4.65 and 6.68 mm whereas the WPC samples values of 1.53, 2.41 and 3.37 mm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 As a kind of biomass materials, woodplastic composites combine the advantages of wood and plastic, which are used in environments where traditional wood products cannot be used for solving the problem that wood products are easy to rot and deform after absorbing water in a damp environment. [10][11][12][13] The use of plastic waste with a single component as the matrix for wood-plastic composites has been considered an effective method to the plastic circular economy. However, due to the poor compatibility of each component in the WAT and the poor dispersibility of wood flour (WF) in the WAT matrix, the use of WAT in the woodplastic composite material is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…With its renewability, biomass resources have been widely concerned and have been used in the preparation of various materials 8,9 . As a kind of biomass materials, wood‐plastic composites combine the advantages of wood and plastic, which are used in environments where traditional wood products cannot be used for solving the problem that wood products are easy to rot and deform after absorbing water in a damp environment 10–13 . The use of plastic waste with a single component as the matrix for wood‐plastic composites has been considered an effective method to the plastic circular economy.…”
Section: Introductionmentioning
confidence: 99%